2012
DOI: 10.1021/nl300183e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Negative Compressibility of Few-Layer Graphene, h-BN, and MoS2

Abstract: We report a novel mechanical response of few-layer graphene, h-BN, and MoS(2) to the simultaneous compression and shear by an atomic force microscope (AFM) tip. The response is characterized by the vertical expansion of these two-dimensional (2D) layered materials upon compression. Such effect is proportional to the applied load, leading to vertical strain values (opposite to the applied force) of up to 150%. The effect is null in the absence of shear, increases with tip velocity, and is anisotropic. It also h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 19 publications
5
59
0
1
Order By: Relevance
“…The interpretation of the observation of Lee et al was supported by the Brownian dynamics simulations of Smolyanitsky et al [59] and by the molecular dynamics simulations of Ye et al [60]. The tip-induced out-of-plane deformation of 2D materials was also experimentally confirmed and systematically studied by Barboza et al [61]. They referred to this effect as "dynamic negative compressibility": When the probe tip slides on these 2D materials, a vertical expansion proportional to the applied normal load appears for dynamical wrinkling of the upper material layers induced by the simultaneous compression and shear from the tip.…”
Section: Dependence Of Friction On Layer Number and Substratementioning
confidence: 79%
“…The interpretation of the observation of Lee et al was supported by the Brownian dynamics simulations of Smolyanitsky et al [59] and by the molecular dynamics simulations of Ye et al [60]. The tip-induced out-of-plane deformation of 2D materials was also experimentally confirmed and systematically studied by Barboza et al [61]. They referred to this effect as "dynamic negative compressibility": When the probe tip slides on these 2D materials, a vertical expansion proportional to the applied normal load appears for dynamical wrinkling of the upper material layers induced by the simultaneous compression and shear from the tip.…”
Section: Dependence Of Friction On Layer Number and Substratementioning
confidence: 79%
“…The thin nanosheets showed greater frictions because of improved susceptibility to outside of plane deformation. Very recently, researchers have reported that the friction force might accelerate flexible, dynamic creasing on the top most layer for different types of nanosheets including graphene, BNNSs and most of TMD layers [438].…”
Section: Thermal Conductivity Of Bnnsmentioning
confidence: 99%
“…The effects of shear forces constitute, thus, an important aspect of FLG physics, which has been recently investigated by different experiments. [1][2][3][4][5][6][7][8][9] Moreover, it has been demonstrated that the electronic properties in FLG can be tuned by changing the layer stacking. A spontaneous gap opening has been detected in three layer graphene (3LG) when passing from Bernal (ABA) to rhombohedral (ABC) stacking.…”
Section: Introductionmentioning
confidence: 99%